Theoretical investigations of ZnO/CdO material – A DFT approach - Jawaher, Rackesh; R, Indirajith; S, Krishnan; Bharani, Bharanidharan; R, Robert; S, Jerome Das (International Journal of Advanced Chemistry, 2018)
The theoretical investigations of ZnO/CdO material were carried out by using ab initio calculations. The bond parameters such as bond lengths, bond angles and dihedral angles were calculated at DFT/B3LYP/LANL2DZ level of theory. The NLO property of the title molecule was calculated using a first order hyperpolarizability calculation. NBO study reveals that the hyperconjucative interactions between the material. Homo-Lumo analysis the charge transfer occurs within the molecule. MEP surface predicts the reactive sites of the present molecule. In addition of Mulliken atomic charges and thermodynamic parameters were also plotted and calculated.